Effect of dietary supplementation of organic and inorganic Se on performance and antioxidant response in commercial broiler chickens. Issue 1 (2nd January 2023) - Prasad, M. V.; Prakash, B.; Narasimha, J.; Rama Rao, S. V.; Raju, M.; Zeba, P.; Sreenivasa Reddy, C.
ABSTRACT: 1. The study was carried out to determine the effects of supplementing organic (OG) or inorganic (IOG) Se to record the performance, immune and anti-oxidant response in broiler chickens. 2. One-day-old Vencobb-400 (50.1 ± 0.84 g; n = 280) male broiler chicks were allocated randomly into seven treatments to give eight replicates containing five chicks each and housed in deep littered floor pens (76 cm × 91 cm) for a period of 42 d. 3. The control diet (CD) was formulated without any Se supplementation (diet I), CD plus 0.15, 0.30 or 0.45 mg/kg OG Se (diets II, III and IV, respectively) and CD plus 0.15, 0.30 or 0.45 mg/kg IOG Se (diets V, VI and VII, respectively). 4. Feed intake (FI), body weight gain (BWG), immune variables and mRNA expression profile of hepatic selenoproteins ( SepW, GSHPx1, TrxR and GSHPx3 ) genes were determined. The BWG, FI and feed conversion ratio did not differ among various dietary treatments. 5. The lipid peroxidation and activity of RBC catalase were lower (P < 0.05) in groups fed diets supplemented OG Se compared to those fed IOG Se and CD. The activity of GSH Px was higher among the groups fed diet supplemented OG Se compared to those groups fed OG Se and CD. However, supplementing diets with OG or IOG Se did not affect humoral or cell mediated immune responses. 6. The expression levels of SepW were higher (P < 0.01) among the groups supplemented with OG Se. Expression levels of GSH-Px1, TrxR and GSHPx3 were higher (P < 0.01) among the groups supplemented with OG Se compared to those groups fed IOG Se or CD. 7. Supplementing OG Se improved the activities of anti-oxidant enzymes and hepatic expression of selenoproteins genes in the present study. However, supplementing OG or IOG Se did not affect growth performance and immune variables in broiler chickens.